Prognostic factors of surgical management for heart failure patients with reduced left ventricular ejection fraction - Mahmoud Yousef Ibrahim Abuharb; Liu Kaiwen; Huang Zhuhui; Zhang Kui; Zheng Jubing; Song Yue; Li Yang; Liu Taoshuai; Dong Ran (Heliyon, 2024)
Objectives: There are many available pharmaceutical and surgical management for Coronary artery disease (CAD) patients. However, coronary artery bypass grafting (CABG) is the preferred treatment modality for CAD patients with low ejection fraction (EF) in view of the more favorable outcomes. This study aimed to determine the associated factors of poor outcomes post-CABG for heart failure patients with reduced left ventricular ejection fraction who underwent on-pump and off-pump CABG. Methods: A retrospective review of CAD patients who underwent isolated on-pump CABG (ONCAB) or off-pump CABG (OPCAB) in Beijing Anzhen Hospital Affiliated with Capital Medical University from January 2013 to March 2021. Only those with confirmed reduced left ventricular ejection fraction (LVEF) ≤40% on preoperative echocardiography were included. By analyzing the clinical and surgical data, postoperative mortality and morbidity, as well as major cardiovascular and cerebrovascular adverse events (MACCE) as endpoints, certain risk factors of the postoperative complications were identified. Results: Out of the 500 patients, 64 developed MACCE, of which 14 (13.6%) occurred in the ONCAB group and 50 (14.0%) in the OPCAB group. Univariate COX regression analysis showed that age ≥65 years, history of diabetes, and preoperative renal insufficiency were independent risk factors for postoperative primary endpoint events in CAD patients with heart failure with reduced ejection fraction (HFrEF). Following the multivariate COX regression analysis, in addition to the above three risk factors, a history of previous percutaneous coronary angiography (PCI) intervention was also a risk factor for the occurrence of the primary endpoints post-CABG. Conclusion: Based on the analysis, significant predictors of post-CABG MACCE in patients with HFrEF included being older than 65 years old, having diabetes, preoperative renal insufficiency, and having previous PCI.